Curcumin-inspired cytotoxic 3, 5-bis(arylmethylene)-1-(N-(ortho-substituted aryl)maleamoyl)-4-piperidones: A novel group of topoisomerase II alpha inhibitors. Issue 19 (1st October 2015) - Jha, Amitabh; Duffield, Katherine M.; Ness, Matthew R.; Ravoori, Sujatha; Andrews, Gabrielle; Bhullar, Khushwant S.; Rupasinghe, H.P. Vasantha; Balzarini, Jan
Graphical abstract: Abstract: Three series of novel 3, 5-bis(arylmethylene)-1-( N -( ortho -substituted aryl)maleamoyl)-4-piperidones, designed as simplified analogs of curcumin with maleic diamide tether, were synthesized and bioevaluated. These compounds displayed potent cytotoxicity towards human Molt 4/C8 and CEM T-lymphocytes as well as murine L1210 leukemic cells. In contrast, the related N -arylmaleamic acids possessed little or no cytotoxicity in these three screens. Design of these compounds was based on molecular modeling studies performed on a related series of molecule in a previous study. Representative title compounds were found to be significantly potent in inhibiting the activity of topoisomerase II alpha indicating the possible mode of action of these compounds. These compounds were also potent antioxidants in vitro and attenuated the AAPH triggered peroxyl radical production in human fibroblasts. Various members of these series were also well tolerated in both in vitro and in vivo toxicity analysis.